Effects of Organic Acid and Probiotics on Cecal Colonization and Immune Responses in Broiler Chickens Challenged with Salmonella Enteritidis - Silva, Tarcísio Macedo; Milbradt , Elisane Lenita; Zame, João Carlos Rodrigues; Padovani, Carlos Roberto; Paz, Ibiara Correia de Lima Almeida; Hataka, Alessandre; Okamoto, Adriano Sakai; Gross, Letícia; Filho, Raphael Lucio Andreatti (International Journal of Poultry Science, 2019)
Objective: This study was designed to compare the effects of continuous supplementation of a pool of Lactobacillus and organic acid on the control of infection by Salmonella Enteritidis (SE) in broiler chickens. Materials and Methods: A total of 240 chickens were distributed in an entirely randomized experimental delineation into eight groups: G1: Basal diet, G2: Basal diet+challenge with SE, G3: basal diet+caprylic acid, G4: Basal diet+caprylic acid+SE, G5: Basal diet+5,7-dichloro-8-quinoline, G6: Basal diet+5,7-dichloro-8-quinoline+SE, G7: Basal diet+pool of Lactobacillus, G8: Basal diet+pool of Lactobacillus+SE. On the 4th, 14th, 24th and 36nd day post infection, blood was collected from the birds for immunological evaluation, ceca were collected for the microbiological evaluation of SE and quantification of interleukin 8 (IL-8) and cecal epithelial samples were collected for histopathological evaluation. Results: At slaughter, all the administered treatments demonstrated the capacity to reduce cecal colonization by SE, as evidenced by the microbiological and histopathological evaluations. The serum levels of IgM were not affected by the various treatments administered but rather only by SE challenge. IL-8 production was not affected by treatment or SE challenge. Conclusion: All the treatments evaluated here showed the capacity to control cecal colonization by SE in broiler chickens and suggest that these treatments may be employed as alternatives to the use of antimicrobials in the control of contamination by SE.